Identification of Atherovulnarable Families in Doctor’s Office at the Primary Health Care Level - Francisco Felipe Hernández Gárciga; Maybi Gómez Sobrino; José Fernández–Britto Rodríguez (Revista Finlay)
Foundation: cardiovascular diseases are identified as an important public health problem in many countries in development and Cuba is not exempted, atherosclerosis is the main cause of the so called great atherosclerotic crisis. Objective: to use a qualitative table for identifying self-vulnerable families, to look for early and late sings of atherosclerosis, in a doctor’s office of the primary health care level. Method: a cross descriptive study was realized in an urban population belonging to the Teaching Polyclinic Dr. Mario Muñoz Monroy, of East Havana. A number of 150 families were studied with all their members for a total of 465 individuals. The study was approached in the period from June 1st to December 31st 2016. The presence of early or subclinical signs of atherosclerosis in children, adolescents and youngsters under 34 years old; other factor were explored as High blood pressure, diabetes mellitus, tobbaccoism, overweightness, obesity and sedentarism. Results: early signs of atherosclerosis were found in 148 of the individuals analyzed which represents 74,32 %. Risk factors of atherosclerosis were found in 317 of the studied adults. Overweightness and obesity prevailed as the most outstanding risk factors, followed by high blood pressure. Fifteen families are considered of a very high priority and 37 families of high priority. Conclusion: complete family study, allows determining early signs and risk factors of atherosclerosis. The use of a qualitative table proposed as a matrix to stratify self-vulnerable families may become an important tool for the basic health group.